Association of Regulatory T Cells with Diabetes Type-1 and Its Renal and Vascular Complications Based on the Expression of Forkhead Box Protein P3 (FoxP3), Helios and Neurophilin-1 - Tahereh Khamechian (Iranian Journal of Allergy, Asthma and Immunology, 2018)
In recent years, it has been recognized that regulatory T cells (Tregs) play a critical role in maintaining immune tolerance. Moreover, the expression of two markers named Helios and neurophilin-1 (NRP-1) has been highlighted in such cells. Helios, an intracellular transcription marker, largely differentiates twomost operative sub group of Tregs, namely naturally occurring (nTreg) and induced (iTreg) Tregs, and NRP-1 is reckoned as a membranous activity marker of Tregs. We aimed to count peripheral mononuclear cells expressing such markers in a group of type 1 diabetes patients to elucidate the possible role of Tregs in the pathogenesis of such disease and its complications. Blood samples from 61 adult patients with type 1 diabetes and 61 sex and age-matched healthy controls were tested to count two types of Tregs, namely naturally occurring and inducible types, according to the expression of cell surface markers of CD4/CD25/CD47–FITC/PE/APC and intracellular markers of FoxP3/Helios–PE-CY5/eFlour450 by flow cytometry, respectively.We also investigated the relation between expression of such markers with HbA1c, urine albumin/creatinine ratio (UACR), and common carotid intima thickness (CIMT). The circulatory frequency of both Helios+ and Helios- T-cells were significantly decreased in patients compared to those in healthy controls (p<0.001). There was also a significant decrease in circulatory frequency of Helios+ NRP-1+ and Helios- NRP-1+ cells in the patients compared to controls (p=0.029). According to expression of Helios and NRP-1 markers, the number and function of both Tregs were decreased in diabetic patients. Moreover, the neurophilin expression was inversely associated with complications of type 1 diabetes.